Chronic Heart Failure in Early Rheumatoid Arthritis Patients Prior to Basic Antirheumatic Therapy - I. G. Kirillova; D. S. Novikova; T. V. Popkova; H. V. Udachkina; E. I. Markelova; Yu. N. Gorbunova; Yu. O. Korsakova; S. N. Gluchova (Столичная издательская компания, 2020)
Aim. To study the clinical manifestations and factors associated with the presence of chronic heart failure (CHF) in patients with early rheumatoid arthritis (RA) prior to anti-inflammatory therapy. Material and methods. The study included 74 patients with valid diagnosis of RA (criteria ACR/EULAR, 2010), 56 women (74%), median age - 54 [46;61] years, disease duration - 7 [4;8] months; seropositive for IgM rheumatoid factor (87%) and/or antibodies to cyclic citrullinated peptide (100%) prior to taking disease modifying anti-rheumatic drugs and glucocorticoids. CHF was verified in accordance with actual guidelines. The assessment of traditional risk factors for cardiovascular diseases, echocardiography, tissue Doppler imaging, carotid artery ultrasound, were carried out before the start of therapy in all patients with early RA. The concentration of NT-proBNP was determined by electrochemiluminescence. The normal range for NT-proBNP was less than 125 pg/ml.Results. CHF was diagnosed in 24 (33%) patients: in 23 patients - CHF with preserved ejection fraction, in 1 patient - CHF with reduced ejection fraction. 50% of patients with RA under the age of 60 were diagnosed with CHF. NYHA class I was found in 5 (21%) patients, class II - in 15 (63%), class III - in 1 (4%). Positive predictive value of clinical symptoms did not exceed 38%. All patients with early RA were divided into two groups: 1 - with CHF, 2 - without CHF. Patients with RA+CHF compared with patients without CHF were older, had higher body mass index, frequency of carotid atherosclerosis, of ischemic heart disease (IHD), hypertension, C-reactive protein (CRP) levels and intima media thickness. Independent factors associated with the presence of CHF were identified by linear regression analysis: abdominal obesity, CRP level, systolic blood pressure, dyslipidemia, carotid intima thickness, IHD. The multiple coefficient of determination was R2=57.1 (R-0.76, p<0.001). Level of NT-proBNP in RA patients with CHF (192.0 [154.9; 255.7] pg/ml) was higher than in RA patients without CHF (77 [41.1; 191.2] pg/ml) and in control (49.0 [33.2; 65.8] pg/ml), p<0.0001 and p=0.01, respectively. To exclude CHF in patients with early RA, the optimal NT-proBNP level was 150.4 pg/ml (sensitivity - 80%, specificity - 79%), the area under the ROC curve = 0.957 (95% confidence interval 0.913-1.002, p<0.001).Conclusion. CHF was detected in a third of RA patients at the early stage of the disease. Factors associated with the presence of CHF were abdominal obesity, CRP level, systolic blood pressure, dyslipidemia, intima media thickness, IHD.